SELEKSI JAMUR TANAH PENGURAI LIGNIN DAN PAH DARI BEBERAPA LINGKUNGAN DI BALI [Selection of Lignin and PAHs Degrading Fungi from Some Environment in Bali] - Subowo, YB; Corazon, Corazon (Research Center for Biology-Indonesian Institute of Sciences, 2010)
An investigation on the selection of soil fungi that degrade lignin and PAHs from some environment in Bali had been done. Some soil fungi are able to degrade lignin compound and PAHs. This fungus can be used to degrade industrial waste containing lignin and hydrocarbon compound. The aim is to obtain fungal capable of degrading lignin and hydrocarbon compounds.The soil samples were taken from mangrove areas, beaches and organic farms to the laboratory for fungal isolation.The isolation of the sample was obtained 20 number isolates. Penicillium sp KSt3 is the highest yield of mycelium.This fungus has ability on poly R-478 degrading as much as 2.3% within 60 minutes. This fungus has laccase activity of 3,32 units/ml and capable of degrading phenanthren (PAH) as much as 85.8% in 8 days.